Differential diagnostics of syncopal conditions - O. N. Dzhioeva; E. V. Reznik; I. G. Nikitin (Кардиоваскулярная терапия и профилактика)
The article is a lecture on modern recommendations of the European Society of Cardiology and the American Heart Association for the diagnosis of syncopal conditions. The article presents the latest information from the 2018 review concerning the definition of syncope, its classification, diagnostics and risk stratification, patient management tactics. The article will be useful both to students, residents, postgraduates of medical universities, and practicing doctors.